Learning Styles in Postgraduate Dentistry Students through the Honey-Alonso Questionnaire - Ortega-Galarza, Máximo (2023)
The objective of the research was to describe the learning styles of students in different specializations at the Postgraduate School of Dentistry at the San Martin University Foundation, Postgraduate Dentistry programs at the University of Cartagena, Postgraduate Dentistry programs at the Cooperative University of Colombia, and at Javeriana University, in the second semester of the year 2022. A descriptive, non-experimental, and comparative research approach was employed, with a simple random sample of 150 students. The instrument used was the CHAEA questionnaire, and data processing was carried out using SPSS V.23. In conclusion, the predominant learning styles across the four universities at the postgraduate level were reflective at 53.3% and theoretical at 47.3%, which are characteristic of a learning process where harmony, tranquility, dedication, and experience are hallmarks of medical sciences.